Use of ash forest biomass combustion as acidity correction and fertility of an Humic Cambisol - Silva, Franciani Rodrigues da; Albuquerque, Jackson Adriano; Gatiboni, Luciano Colpo; Costa, André da (Revista de Ciências Agroveterinárias, 2013)
Many industries use the biomass combustion for power generation, a process that produces a lot of ash. The objective of this study was to evaluate the effect of biomass combustion ash as a corrective for acidity and as a soil fertilizer, comparing it with the effects of lime, in the Humic Cambisol cultivated with Eucalyptus dunnii. The experiment was conducted in a greenhouse, in a completely randomized experimental design, with the following treatments: 1- control; 2- forest biomass ash at a dose of 11 Mg ha-1; 3- forest biomass ash of 22 Mg ha-1; 4- Lime at a dose of 8.5 Mg ha-1; 5- Lime at a dose of 17 Mg ha-1. Eucalyptus dunnii seedlings were planted in pots and cultivated for 70 days in a greenhouse. After the chemical and physical attributes of soil, dry mass produced and the chemical composition of plant tissue were evaluated. The addition of ash forest biomass can be used in highly buffered soils because: it does not alter the degree of flocculation and the acidity of the soil; it’s a source of K, P and Ca. The application of lime neutralizes soil acidity and provides more P for the eucalyptus. The early growth of Eucalyptus in fertilized soil, is not changed by applying ashes or lime.